Consent to autopsy for neonates. Issue 1 (1st July 2001) - McHaffie, H E; Fowlie, P W; Hume, R; Laing, I A; Lloyd, D J; Lyon, A J
Abstract : OBJECTIVES: To determine parents' views on autopsy after treatment withdrawal. DESIGN: Face to face interviews with 59 sets of bereaved parents (108 individual parents) for whose 62 babies there had been discussion of treatment withdrawal. RESULTS: All except one couple were asked for permission for postmortem examination; 38% refused. The main reasons for declining were concerns about disfigurement, a wish to have the child left in peace, and a feeling that an autopsy was unnecessary because the parents had no unanswered questions. The diagnosis, the age of the child, and the approach of the consultant appeared to influence consent rates. Of those who agreed to autopsies, 92% were given the results by the neonatologist concerned. Whether or not they had agreed to the procedure, at 13 months no parent expressed regrets about their decision. CONCLUSIONS: Autopsy rates in the East of Scotland stand at 62%. Parents' perceptions are an important element in consent to postmortem examination.